ASIAB Clothing Media for Early Childhood Disaster Preparedness - Marisa Ifkarina, Putri Diana; Kartika Rinakit, Adhe (Universitas Nahdlatul Ulama Surabaya, 2021)
Indonesia is a country that has a high risk of natural disasters. Lack of natural ability to save themselves results in an enormous potential for children to suffer the most when a disaster occurs. Natural disaster preparedness needs to be introduced to children from an early age. Children are no longer a concern as victims who suffer the most but need to save themselves when in danger. The purpose of developing ASIAB clothing media is to determine the development, effectiveness, and feasibility of ASIAB clothing media for early childhood disaster preparedness. This type of research uses Research and Development (R&D) with the ADDIE development model. The research subjects were media experts, material experts, and 30 teachers in TK Surabaya and Sidoarjo, East Java, Indonesia. Data collection was carried out using structured interview techniques and online questionnaires via google form accompanied by video supporting procedures for using ASIAB clothing media. Analyzing the feasibility and effectiveness of the ASIAB clothing media used qualitative and quantitative descriptive analysis with a predetermined percentage of the assessment. The results obtained show that the ASIAB clothing media is feasible in learning early childhood disaster preparedness. The feasibility of testing by media experts obtained results with the criteria